Comparison of Bispectral Index-Guided Individualized Anesthesia with Standard General Anesthesia on Inadequate Emergence and Postoperative Delirium in Elderly Patients Undergoing Esophagectomy: A Retrospective Study at a Single Center - Yang, Yichen (Med Sci Monit, 2020)
BACKGROUND: Elderly patients are susceptible to general anesthetics, with a higher bispectral index (BIS) at loss of consciousness (LOC) achieved by propofol infusion compared with young patients. Overexposure to general anesthetics can have adverse effects such as inadequate emergence and postoperative delirium (PD). This study aimed to compare the effects of BIS-guided individualized anesthesia with standard general anesthesia on emergence and delirium after esophagectomy. MATERIAL/METHODS: Data on 161 elderly patients undergoing esophagectomy for cancer were retrospectively obtained from electronic medical records. We performed propensity score matching analysis between patients receiving individualized anesthesia (BIS value maintained at about 10 less than the value at LOC) and those receiving standard anesthesia (BIS value maintained at 40–60). In addition, we conducted univariate and multivariate logistic analyses in the entire cohort. RESULTS: Patients receiving individualized anesthesia had higher BIS values and a lower propofol requirement during surgery than those receiving standard general anesthesia (P<0.05). The overall incidences of inadequate emergence and PD were 37.9% and 18.0% (n=161), respectively. Logistic regression analysis revealed that the independent risk factors for PD were organic brain disease (odds ratio [OR] 6.308; 95% confidence interval [CI] 2.458–16.187) and inadequate emergence (OR 4.063; 95% CI 1.645–10.033). CONCLUSIONS: BIS-guided individualized anesthesia (lighter) does not reduce inadequate emergence or PD compared with standard general anesthesia in elderly patients undergoing esophagectomy. Independent risk factors for PD include organic brain disease and inadequate emergence.